Elucidating the molecular epidemiology of trypanosomes for evidence-based tsetse-vector control in the Shimba Hills human-wildlife-livestock interface, Kenya - Bastos, Armanda D.S. (University of Pretoria, 2022)
Thesis (PhD (Entomology))--University of Pretoria, 2022.